Question

Asked Oct 28, 2019

10 views

2x-3y=12 2x+6y=-24

Step 1

The give system of equations are as follows

*2x – 3y = 12 *––––––(1)*2x + 6y = –24* ––––––(2)

Step 2

Solving above equations by using substitution method.

Isolate *x *from equation (1) as shown below:

Step 3

Now substitute the above value of *x *in the 2nd equation, we get

Tagged in

Q: The cost C in dollars of removing p% of the air pollutants in the stack emissions of a utility compa...

A: The given equation of the cost C (in dollars) in removing p percent of the air pollutants in the sta...

Q: x+9<0 or 3x>-9 solve for the compound inequality how do i solve this ?

A: The given inequality is

Q: Algebra Question

A: Plug f^-1(x)=(5x+15)/(x-1).

Q: In the equation x= y3-10 is y a function of x? I have no idea what this is asking me?

A: Rewrite the given as follows.

Q: Reading Graphs and the Rectangular C System Complete a table of solutions to a linear equation in tw...

A: Click to see the answer

Q: Solve . Don't forget to Check! 1/y+2/y=3

A: Given,

Q: 4(x+2)-5=3 What is the value of x?

A: Click to see the answer

Q: (ax + by)(cx - dy) In the expression above, a, b, c, and d are non-zero constants and ad=bc. If ac=1...

A: Click to see the answer

Q: How to find feasible region?

A: Given,